Pengaruh keputusan keuangan, struktur kepemilikan, dan tingkat suku bunga terhadap nilai perusahaan property dan real estate yang go public - Andi Novianto; Rr Iramani (Journal of Business & Banking, 2015)
The companys value is related to the stock price, showing the value that investors are willing to pay. To increase the stock price, the company should make good financial decisions and ownership structure. In addition, external factors also need to be consi-dered, one of which is the interest rate. This study aimed to examine the effect of finan-cial decisions, ownership structure, and the interest rate on the value of go public property and real estate companies. The sample consists of 45 property and real esate companies listed on Indonesia Stock Exchange in 2009-2013 periods. It uses purposive sampling method in determining the sample and multiple linear regression analysis for analyzing the effect of independent variables on the dependent variable. The results indicate that investment decisions are measured by Total Assets Growth insignificant positive effect on the companys value. Financing decision is measured by Debt to Eq-uity Ratio, dividend policy is measured by the Dividend Payout Ratio, and institu-tional ownership has significant positive effect on the companys value, while mana-gerial ownership and interest rate have insignificant and negative effect on the compa-nys value.